2015
DOI: 10.1089/bio.2014.0073
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Cryopreservation of a Giant Panda Skeletal Muscle-Derived Cell Line

Abstract: The giant panda Ailuropoda melanoleuca is an endangered species and is a symbol for wildlife conservation. Although efforts have been made to protect this rare and endangered species through breeding and conservative biology, the long-term preservation of giant panda genome resources (gametes, tissues, organs, genomic libraries, etc.) is still a practical option. In this study, the giant panda skeletal muscle-derived cell line was successfully established via primary explants culture and cryopreservation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In our study, muscle cells obtained showed more than 90% viability after thawing and demonstrated relatively moderate population doubling times (52.98 h) compared to other muscle cell lines derived from Giant Panda (33.8 h) [40] and triploid olive founder (69.88 h) [41], respectively. Tese results indicated that WYSM cells were successfully cryopreserved and revived.…”
Section: Discussionmentioning
confidence: 55%
“…In our study, muscle cells obtained showed more than 90% viability after thawing and demonstrated relatively moderate population doubling times (52.98 h) compared to other muscle cell lines derived from Giant Panda (33.8 h) [40] and triploid olive founder (69.88 h) [41], respectively. Tese results indicated that WYSM cells were successfully cryopreserved and revived.…”
Section: Discussionmentioning
confidence: 55%
“…Cryopreservation of cell lines plays an important role in preserving the genetic resources of threatened species (Cetinkaya et al 2011). In our study, the obtained muscle cells showed more than 90% viability after post-thaw and demonstrated a relatively moderate population doubling times (52.98h) compared to other muscle cell lines, derived from Giant Panda (33.8h) (Yu et al 2015) and triploid olive ounder (69.88h) (Peng et al 2016), respectively. These results indicated that the WYSM cells have been successfully cryopreserved and revived.…”
Section: Discussionmentioning
confidence: 56%
“…This bank preserves plant seeds of 10,000 species, animal germplasms, macrofungi, and microorganisms. In addition, Chinese academic institutes now explore the cryopreservation option for cell lines of wild animals, such as Bengal tigers (Guan et al 2010 ) and pandas (Yu et al 2015 ).…”
Section: Biobanks By Countriesmentioning
confidence: 99%